Lipid Profile among Pregnant and Non-Pregnant Women in Rajshahi City - Begum, Bedowra; Rupa, Shamima Nazneen; Sayem, ASM; Akhter, Shahnaz; Sharmin, Susmita; Jhumu, Sumayra; Khatun, Mst Fatema (TAJ: Journal of Teachers Association, 2023)
Background: Pregnancy is a physiological state with rapid hormonal and metabolic changes that helps the growth and survival of the fetus properly. However, biochemical profile derangement may lead to pregnancy complications and, eventually maybe, death. Objectives: This study aimed to investigate whether lipid profile (Serum total cholesterol, Serum triglyceride, HDL-C, and LDL-C) during 3rd trimester of pregnancy differs from non-pregnant women of similar reproductive life. Materials & Methods: This cross-sectional type of comparative study was carried out in the Physiology Department of Rajshahi Medical College in collaboration with the Maternity and Child Welfare Centre (MCWC), Rajshahi, over a period of 12 months from January 2019 to December 2019 among the pregnant and non-pregnant women to investigate the lipid profile during 3rd trimester of pregnancy. Approval from the Ethical Review Committee (ERC) was obtained prior to the commencement of the study. A pre-designed, validated, structured questionnaire was used to gather information from 120 women by purposive sampling technique. Of them, 60 were pregnant women, and 60 were non-pregnant healthy women. Results: The Results showed that the total serum cholesterol, serum triglyceride, and LDL-C were raised among pregnant women compared to non-pregnant women, and these were statistically significant (p < 0.001). But no significant difference in HDL-C was found between the two groups (p > 0.05). In this study, it was found that there was a substantial raised in lipid profile in the 3rd trimester of pregnancy compared with non-pregnant healthy women. So, regular monitoring of the lipid profile of pregnant women should be done to avoid adverse pregnancy outcomes. Conclusion: Total metabolism is increased due to the needs of the growing fetus and the uterus. Basal metabolic rate may be increased up to 30% higher than that of the average for non-pregnant women. TAJ 2022; 35: No-2: 51-58